Emerging role for nuclear rotation and orientation in cell migration - Maninová, Miloslava; Iwanicki, Marcin P; Vomastek, Tomáš (Cell adhesion & migration, 2014)
Nucleus movement, positioning, and orientation is precisely specified and actively regulated within cells, and it plays a critical role in many cellular and developmental processes. Mutation of proteins that regulate the nucleus anchoring and movement lead to diverse pathologies, laminopathies in particular, suggesting that the nucleus correct positioning and movement is essential for proper cellular function. In motile cells that polarize toward the direction of migration, the nucleus undergoes controlled rotation promoting the alignment of the nucleus with the axis of migration. Such spatial organization of the cell appears to be optimal for the cell migration. Nuclear reorientation requires the cytoskeleton to be anchored to the nuclear envelope, which exerts pulling or pushing torque on the nucleus. Here we discuss the possible molecular mechanisms regulating the nuclear rotation and reorientation and the significance of this type of nuclear movement for cell migration.
Keywords: cell polarity; migration; myosin; nuclear reorientation; dynein; LINC; focal adhesions; actin; FAK; microtubules